Hyponatremia In Ischemic Stroke Patients And Its Relationship To Clinical Outcomes In Such Patients - Zafar, Maria; Jalil, Aneza; Ghaffer, Amber; Yousaf, Mahnoor; Batool, Sadia (Journal of Rawalpindi Medical College, 2024)
Objective: To quantify the frequency of hyponatremia in patients with ischemic stroke, and to compare patient outcomes according to the frequency and severity of hyponatremia. Methods: A descriptive cross-sectional study was carried out for a period of six months (11-12-2020 to 10-06-2021) at the department of Medicine and Neurology, PIMS, Islamabad.A total of one hundred and seventy-nine (n=179) acute ischemic stroke patients of either gender between age 16-80 years were enrolled. Stroke severity was measured through the National Institute of Health stroke scale score and serum sodium was measured at the time of admission in all patients to diagnose hyponatremia. All patients with hemorrhagic stroke, having previous history of stroke, recent head injury, CNS infection, already using sodium lowering diuretics, or with end-stage diseases like Heart failure, chronic kidney disease and decompensated liver diseases were excluded from the study. Primary outcome measures were in-hospital mortality and duration of hospital stay (LOS). Results: Hyponatremia was found in 30.1% (n=54/179) patients at the time of admission. Overall, in-hospital mortality in the study population was 11.7% (n=21/179) and the mean length of hospital stay was 6.9 days ± 2.5 SD. Mortality was significantly higher in patients with severe stroke (based on NIHSS score) (P=0.010) and severe hyponatremia (serum Na levels below 120 mEq/litre) (P=0.001). Mean hospital stay was also significantly longer in patients with severe stroke based on NIHSS score (P=0.001) and severe hyponatremia (P=0.048). Conclusions: A remarkable proportion (30.1%) of acute ischemic stroke patients had hyponatremia. In-hospital mortality was significantly higher and the length of hospital stay LOS was significantly longer in patients with severe stroke and severe hyponatremia. Keywords: Hyponatremia, Ischemic stroke.